How to reach a wider audience with open access publishing: what research universities can learn from universities of applied sciences - Woutersen-Windhouwer, Saskia; Kuijper, Jaroen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
In Amsterdam, the libraries of the University of Amsterdam (UvA) and the Amsterdam University of Applied Sciences (AUAS) cooperate closely. In this cooperation, the differences between a research university (i.c. UvA) and a university of applied sciences (i.c. AUAS) become particularly clear when we look at the aim and implementation of open access policies. The open access plan of the AUAS removes not only financial and legal barriers, but also language barriers. This makes the research output FAIR (findable, accessible, interoperable and reusable) to the primary target group of the product, and more importantly, it enables interaction between the AUAS and a wide audience, consisting of researchers from other disciplines, and a wide range of professionals, enterprises, civil servants, schools and citizens. In the search for co-financing by enterprises and other stakeholders, and to fulfil their valorisation requirements, these target groups are currently becoming more important for research universities as well. Here, we show what research universities can learn from the open access policy of the AUAS.